102k views
2 votes
Factor-3/4 out of 3/2x-9/4y

User Sasho
by
5.7k points

1 Answer

5 votes

For this case we must factor
- \frac {3} {4}of the following expression:


\frac {3} {2} x- \frac {9} {4}y

By law of signs of multiplication it is fulfilled that:


- * - = +\\- * + = -

So we have to:


- \frac {3} {4} * (- 2) = + \frac {6} {4} = + \frac {3} {2}\\- \frac {3} {4} * 3 = - \frac {9} {4}

Thus, by factoring we have:


- \frac {3} {4} (- 2x + 3y)

Answer:


- \frac {3} {4} (- 2x + 3y)

User Grettke
by
5.2k points